Institutionalization of Dowry in India: Social Custom or Modern Malaise? - Nithya N.R (International Journal of Science and Research (IJSR), India, 2013)
The purpose of this paper is to examine the complex social and cultural practice of dowry in India. Dowry is a payment of cash or valuable gifts from the bride’s family to the bridegroom upon marriage. Dowry is one of social evils which India needs to fight and eradicate totally. The paper argues that this menace of Dowry has become a social menace in modern India leading to the oppression on women, physical violence on the bride, causing a financial and emotional stress on the parents of the bride, marital conflict and so on. At the present, the practice of giving dowry is widespread and deep-rooted in the Indian society. Paying dowry at the time of marriage is almost considered to be universal rule and dowry demands are rising.